Finite element approximation of the first eigenvalue of a nonlinear problem for some special domain - Gabriella Bognár (Electronic Journal of Qualitative Theory of Differential Equations, 2000)
In this paper we present a method for the numerical approximation of the smallest eigenvalue of a nonlinear eigenvalue problem using the finite element method. Numerical results are presented for some special domains when the domain is bounded by a square, a ''circle'', a ''semicircle'', or a quadrant of a ''circle''. We compare the exact solutions with the approximate solutions when the exact solutions are known. We show a connection among the first eigenvalues related to different domains.